Anatomical concept of the real location of upper intermuscular absceses.: Therapeutical implications. - Veirano, Gustavo; Bermúdez, Jorge; Rompani, Omar (Cirugía del Uruguay, 1988)
Authors discuss the real localion of !he so-called intermuscular abscesses, based on previous descriptions they have made of ano-recto-perineal musculature. They point out !he intimate adherence of longitudinal rectum fibers to circular ones, and also describe longitudinal fibers that join fibers froma the levator ani and then descend and form the anal intermuscular septum. Based on anatomical disseclions on fresh cadaveric pieces and others kept in formaldeyde, they suggest that the upper diffusion of suppuralive processes of cryptic origin is made outside the longitudinal fibers, thus being located between the fascia reclis and the longitudinal layer, or on the outside between the pelvic fascia and the levator ani